Haptically facilitated bimanual training combined with augmented visual feedback in moderate to severe hemiplegia - Boos, Amy (Conf Proc IEEE Eng Med Biol Soc, 2011)
This study describes the design and feasibility testing of a hand rehabilitation system that provides haptic assistance for hand opening in moderate to severe hemiplegia while subjects attempt to perform bilateral hand movements. A cable-actuated exoskeleton robot assists the subjects in performing impaired finger movements but is controlled by movement of the unimpaired hand. In an attempt to combine the neurophysiological stimuli of bilateral movement and action observation during training, visual feedback of the impaired hand is replaced by feedback of the unimpaired hand, either by using a sagittaly oriented mirror or a virtual reality setup with a pair of virtual hands presented on a flat screen controlled with movement of the unimpaired hand, providing a visual image of their paretic hand moving normally. Joint angles for both hands are measured using data gloves. The system is programmed to maintain a symmetrical relationship between the two hands as they respond to commands to open and close simultaneously. Three persons with moderate to severe hemiplegia secondary to stroke trained with the system for eight, 30 to 60 minute sessions without adverse events. Each demonstrated positive motor adaptations to training. The system was well tolerated by persons with moderate to severe upper extremity hemiplegia. Further testing of its effects on motor ability with a broader range of clinical presentations is indicated.